The Effectiveness of the Frontloading Strategy on Students’ Vocabulary Mastery in Junior High School - Adhista Salsabila; Lidiyatul Izzah; Umi Ati (English Language in Focus (ELIF), 2022)
The researcher intends to assess students' ability to master vocabulary by implementing the Frontloading approach in class eight of SMPN 21 Tangsel. The Frontloading approach was used to increase students' English vocabulary. The Pre-experimental approach is used in this study, with one design pre-test and post-test consisting of eight encounters including treatment. Sampling was used to collect samples from 40 students in class VIII-1. The average score of students' progress for their vocabulary in synonyms was 41.35 on the pre-test and 68.22 on the post-test, while the antonym was 49.50 on the pre-test and became 68.95 in the post-test, according to the findings of this study. And the overall pre-test score is 52.40, with a post-test score of 78.12. This is supported by test results that are higher than the t-table value (14.71> 1.665). As a result, the alternative is chosen and the Null Hypothesis is rejected. Based on the findings of the data analysis, the researchers determined that using the frontloading strategy increases students' vocabulary in grade eight. According to the findings of this study, the frontloading method is an effective way to increase students' vocabulary.